Politik Hukum Suksesi Yogyakarta: Benturan Legitimasi antara Sabdaraja dan Perdais Nomor 2 Tahun 2015 - Ali Ridho; Tiara Tahta Anindhita; Saffiya Hisaan Irhamna Pranowo; Widhya Facitha Rezaliany; Arofah Minasari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The Special Region of Yogyakarta has unique governmental characteristics, where the reigning Sultan automatically serves as Governor. Problems arose when the Sultan issued a Sabdaraja (Decree) that opened the possibility of leadership succession to women. This customary policy potentially contradicts Special Region Regulation Number 2 of 2015, which normatively requires the Governor to be male. This study aims to examine the implications of the Sultan's dual authority on leadership legitimacy conflicts, identify conflicts between customary law and state law, and formulate possible regulatory harmonization to ensure stable government succession. The research method used is descriptive qualitative with a literature study approach. Data were obtained through a review of laws and regulations, Sabdaraja documents, scientific articles, and news reports related to the dynamics of the Yogyakarta Palace. The results indicate that the basic normative differences between customary law and positive law have the potential to create dual legitimacy conflicts and legal uncertainty regarding the legitimacy of future gubernatorial candidates.